INTRACEREBRAL HEMORRHAGE (ICH) INCIDENCE PROFILE IN JEMURSARI ISLAMIC HOSPITAL DURING THE PERIOD 2017-2019 - Hidayatullah Hidayatullah; Shobihatus Syifak; Choirotussanijjah Choirotussanijjah (Denta Journal Kedokteran Gigi, 2022)
Background: Intracerebral hemorrhage or ICH or hemorrhagic stroke is caused by bleeding within brain parenchyma. Riskesdas reported that stroke patients in Indonesia experienced an increase from 7 permil in 2013 to 10.9 permil in 2018. Mortality rate for ICH is estimated 40% in 1 month and 54% in 1 year. Rumah sakit Islam Jemursari (RSI) is the only type B hospital in Wonocolo sub-district, Surabaya city. This study aimed to analyze the pattern of incidents and variations of ICH at RSI Jemursari Surabaya.Method: This was a descriptive observational study. Medical record data is collected from 2017-2019. The data were obtained from medical records section of total number of ICH, gender, age and outcome of patients. Furthermore, data is analyzed and illustrated through a bar chart and the frequency of mortality is calculated.Results: Total ICH patients at Jemursari Hospital were 310 with 192 male patients and 118 female patients over 3 years. Meanwhile, the most groups experienced ICH were 45-64 years, followed by +65 age group. This is consistent with several epidemiological studies related to ICH, where the incidence of ICH increases with increasing age. The mortality rate for ICH patients, in the 2017-2019 periode, was around 23-30%.Conclusion: It can be concluded that male more susceptible to ICH than female subjects. Meanwhile, the mortality rate for ICH patients ranged from 23-30% in the 2017-2019 period. It is necessary to carry out further evaluation related to other data from the patient. So it could describe incidence rate as well as an overview of the ICH profile at RSI Jemursari.